EFEKTIVITAS QAILULLAH (TIDUR SIANG) DI SD ISLAM TIRTAYASA - Munawaroh; Farida Nazmi Nurlaila; Linda Nuraidah; Nurul Hidayah; Sefiana Aulia Rahmatika; Shahnaz’s Approdita Aulia Cintana; Siti Maimunah; Uswatun Hasanah; Zulfah Afinda Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the effectiveness of the qailullah program in supporting effective learning at SDIT Tirtayasa. The qailullah program is one of the school's flagship programs, implemented regularly by providing students with time to rest and take a short nap before continuing their learning activities. This program is designed to maintain students' physical fitness and psychological well-being so that they can participate in the learning process more optimally. This study employed a descriptive qualitative approach to obtain an in-depth understanding of the implementation of the qailullah program and its impact on the teaching and learning process. Data were collected through observations, interviews, and documentation. The research participants consisted of the principal, teachers, and students who were directly involved in the implementation of the qailullah program. The collected data were analyzed through data reduction, data display, and conclusion drawing. The findings revealed that the qailullah program made a positive contribution to the learning process at SDIT Tirtayasa. The program provided students with adequate rest, enabling them to return to class feeling refreshed, focused, and motivated. Teachers also reported that classroom conditions became more orderly and conducive after the qailullah session. Furthermore, students demonstrated increased attention to learning materials, greater participation in classroom activities, and improved understanding of the lessons. Based on the findings, it can be concluded that the qailullah program plays an important role in supporting effective learning at SDIT Tirtayasa. In addition to promoting students' health and well-being, the program helps create a comfortable learning environment, allowing the teaching and learning process to take place more effectively.